2023
DOI: 10.13075/ijomeh.1896.02132
|View full text |Cite
|
Sign up to set email alerts
|

A narrative review on factors associated with job interruption during pregnancy

Loïc Brunner,
Peggy Chagnon Krief,
Isabelle Probst
et al.

Abstract: Most women continue to work during pregnancy. However, some of them have to stop working before giving birth. Absence from work poses several challenges for employers and employees, as well as for society. The literature on absence from work during pregnancy and its determinants remains inconsistent and rather scarce. To conduct a narrative literature review on the factors associated with work interruption and on existing interventions aimed at reducing the absence prevalence during pregnancy. The review refer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…• when there is a non-conforming risk analysis report (N = 24) 62.5 (15) • when there is no realized any risk analysis (N = 224) 37.05 (83)…”
Section: Proportion Of Worktations For Which the Return To Work Was P...mentioning
confidence: 99%
See 1 more Smart Citation
“…• when there is a non-conforming risk analysis report (N = 24) 62.5 (15) • when there is no realized any risk analysis (N = 224) 37.05 (83)…”
Section: Proportion Of Worktations For Which the Return To Work Was P...mentioning
confidence: 99%
“…For instance, in Denmark, Norway, France, and Spain, studies reported that pregnant workers have higher levels of absence than non-pregnant workers [12][13][14]. On the other hand, not all these absences are caused by pathologic problems or symptoms related to pregnancy but by inadequate working conditions [15]. Several studies show a strong association between strenuous working conditions (such as work postures, carrying heavy load, shift work, night work, increasing working hours, and occupational strain) and work interruptions [13,[16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%